The transformations of Slobozhanschinа Region folk pottery ornamentation in the nineteenth century - Щербань, Анатолій (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
Two most detailed scientific sources for studying the processes of transformation in the ornamentation of Slobodian clay products were analyzed – published reports by Alexander Tverdokhlebov (1883) and Lev Sokolovsky (1885). Presented characteristic decoration of ceramics in four pottery centers : the settlement Horokhuvatka and the village Gavrilovka, Izum (modern Kharkiv region), Okhtyrka (modern Sumy region) and settlement of Kotelva (modern Poltava region). Recorded its dynamic and multi directional evolution in each of these centers. A conclusion was made that most of the rich ceramics ornaments of the ninetieth century in studied specified localities were innovative and originated by copying them in aforementioned century. Except Kotelva tiles ornamentation which was introduced to pottery earlier. Conclusion was made that spread of distinctive decor types and „fashions» in most of the aforementioned pottery centers was heavily influenced by demand. The causes of individual transformations were retraced. For example, the fact that ornamentation of the vessels was changed to improve visual appeal of the products, introducing fashionable and appealing elements, motives and techniques for buyer to occupy its own segment of the significantly expanding market.